An Approach to Resolving Contention Problem in an Optical Burst Switching WDM Network - Bojović, R.; Pevac, D.; Petrović, I. (Elektronika ir Elektrotechnika, 2008)
We propose to use a new wavelength allocation (WA) scheme with deflection routing, whilst investigating its influence to the optical burst switching (OBS) node performance. To evaluate the burst blocking probability we have developed the analytical and simulation models of an OBS node performing WA scheme in conjunction with the deflection routing. The results obtained from the analytical and simulation models indicate that the WA scheme yields to decrease the deflected burst blocking probability and reduces the cost of OBS node in WDM optical network. Ill. 6, bibl. 7 (in English; summaries in English, Russian and Lithuanian).